Deciphering Mary Stuart's lost letters from 1578-1584. Issue 2 (4th March 2023) - Lasry, George; Biermann, Norbert; Tomokiyo, Satoshi
Abstract: Mary Stuart, Queen of Scots (1542–1587), has left an extensive corpus of letters held in various archive collections. There is evidence, however that other letters from Mary Stuart are missing from those collections, such as letters referenced in other sources but not found elsewhere. In Under the Molehill – an Elizabethan Spy Story, John Bossy writes that a secret correspondence with her associates and allies, prior to its compromise in mid-1583, was "kept so secure that none of it has survived, and we don't know what was in it." We have found over 55 letters fully in cipher in the Bibliothèque nationale de France, which, after we broke the code and deciphered the letters, unexpectedly turned out to be letters from Mary Stuart, addressed mostly to Michel de Castelnau Mauvissière, the French ambassador to England. Written between 1578 and 1584, those newly deciphered letters are most likely part of the aforementioned secret correspondence considered to have been lost, and they constitute a voluminous body of new primary material on Mary Stuart – about 50, 000 words in total, shedding new light on some of her years of captivity in England.